The Money Market and Monetary Management - Woodworth, George Walter (New York : Harper & Row, 1972)
Emphasis in the book is placed on the theoretical framework and on the analytical approach to policy determination. Another feature of the book is its primary concern with the short term money market rather than with the long term capital market.
Includes bibliographies.
osc 28/8/17
Loans
Keywords: Money market; Monetary policy